Plasma-Induced Hetero-Nanostructures on a Polymer with Selective Metal Co-Deposition - Ko, Tae-Jun; Oh, Kyu Hwan; Moon, Myoung-Woon (WILEY, 2015)
Plasma-induced pattern formation is explored on polyethylene terephthalate (PET) using an oxygen plasma glow discharge. The nanostructures on PET are formed through preferential etching directed by the co-deposition of metallic elements, such as Cr or Fe, sputtered from a stainless-steel cathode. The local islands formed by metal co-deposition have significantly slower etching rates than those of the pristine regions on PET, generating anisotropic nanostructures in pillar-or hair-like form during plasma etching. By covering the cathode with the appropriate material, the desired metallic or polymeric elements can be co-deposited onto the target surfaces. When the cathode is covered by a relatively soft material composed of only carbon and hydrogen, such as polystyrene, nanostructures typically induced by preferential etching are not observed on the PET surface, and the surfaces are uniformly etched. A variety of metals, such as Ag, Cu, Pt, or Si, can be successfully co-deposited onto the PET surfaces by simply using a cathode covered in the desired metal; high-aspect-ratio nanostructures coated with the co-deposited metal are subsequently formed. Therefore this simple single-step method for forming hetero-nanostructures-that is, nanoscale hair-like polymer structures decorated with metals-can be used to produce nanostructures for various applications, such as catalysts, sensors, or energy devices.
Keywords: INDUCED SPUTTERING YIELDS; ENERGY-DEPENDENCE; SURFACES; TEMPLATELESS; FABRICATION; NANODOTS